Chemical evolution of elliptical galaxies I: supernovae and AGN feedback. Issue 1 (12th November 2022) - Molero, Marta; Matteucci, Francesca; Ciotti, Luca
ABSTRACT: We study the formation and evolution of elliptical galaxies and how they suppress star formation and maintain it quenched. A one-zone chemical model which follows in detail the time evolution of gas mass and its chemical abundances during the active and passive evolution is adopted. The model includes both gas infall and outflow as well as detailed stellar nucleosynthesis. Elliptical galaxies with different infall masses, following a down-sizing in star formation scenario, are considered. In the chemical evolution simulation, we include a novel calculation of the feedback processes. We include heating by stellar wind, core-collapse supernovae (SNe), Type Ia SNe (usually not highlighted in galaxy formation simulations), and active galactic nucleus (AGN) feedback. The AGN feedback is a novelty in this kind of models and is computed by considering a Bondi-Eddington limited accretion onto the central supermassive black hole. We successfully reproduce several observational features, such as the [α/Fe] ratios increasing with galaxy mass, mass-metallicity, M BH –σ and M BH – M * relations. Moreover, we show that stellar feedback and in particular Type Ia SNe, has a main role in maintaining quenched the star formation after the occurrence of the main galactic wind, especially in low-mass ellipticals. For larger systems, the contribution from AGN to thermal energy of gas appears to be necessary. However, the effect of the AGN on the development of the main galactic wind is negligible, unless an unreasonable high-AGN efficiency or an extremely low-stellar feedback are assumed. We emphasize the important role played by Type Ia SNe in the energy budget of early-type galaxies.